Théo Martin, Les sentinelles de l’étable. Robotisation de la traite et nouvelle division du travail dans l'élevage laitier français - Théo Martin (Revue de la Régulation)
This PhD thesis offers a critical analysis of the promises made by agricultural robotics with regard to improving or even replacing human labour. This work starts with a historical review of the modernisation of dairy production in two dairy farming regions (1945-2020). The development of milking machinery appears to be associated with an increase in the division of labour on-farm and off-farm. Since the late 2000s, the robotization of milking has been steadily developing which contributes to intensify the technical and social redistribution of labour. This division of labour goes along with a new time organisation of work required to put dairy production into a flow process. Wage employment becomes more attractive and for farmers the window of working time widens which contributes to intensify his self-exploitation.